Taxonomy of some Indian and Pacific oceans Corticium, with the description of three new species from Western Australia (Porifera: Homosclerophorida) - Muricy, Guilherme; Sarmento, Karen; Lage, Anaíra; Almeida, Ana Carina; Fromont, Jane (Zootaxa, 2021)
The sponge genus Corticium has important evolutionary significance and great pharmacological potential, but its diversity remains poorly known. In this contribution we redescribe two poorly-known Indian and Pacific oceans species, viz., Corticium simplex and C. bargibanti, and describe three new species of Corticium from Western Australia. We observed for the first time the presence of rare calthrops in C. simplex, which has a wide distribution and may be a species complex. The three new species are mainly characterized by their spiculation: Corticium furcatum sp. nov. has large calthrops and exclusive candelabra with bifurcated rays in the apical actine; C. monolophum sp. nov. has large monolophose calthrops, smooth calthrops and candelabra; and C. verticillatum sp. nov. has acanthocalthrops with verticillated spines, which are exclusive to this species within the genus. The diversity of Corticium is raised to 11 species worldwide, but it still remains highly underestimated. A key to all valid species is here provided.